Osbeckia brachystemon Naudin (Melastomataceae): Addition to the Flora of Odisha, India - N., Sanath Kumar; Devi, Rajkumari Supriya; Marndi, Sugimani; Kumar, Sanjeet (Indian Forester, 2024)
No Abstract.